Diet and Physical Activity Behaviors in Primary Care Patients with Recent Intentional Weight Loss. Issue 18 (15th September 2017) - Barone Gibbs, Bethany; Tudorascu, Dana; Bryce, Cindy L.; Comer, Diane; Fischer, Gary S.; Hess, Rachel; Huber, Kimberly A.; McTigue, Kathleen M.; Simkin-Silverman, Laurey R.; Conroy, Molly B.
Abstract : ABSTRACT: Lifestyle habits of primary care patients with recent, intentional weight loss are unclear and need to be better understood to aid in translational health promotion efforts. We aimed to characterize diet and exercise habits in primary care patients with recent, intentional weight loss, comparing those with greater (≥10%) versus lesser (5% to <10%) weight loss. This was a cross-sectional analysis of baseline data from a randomized trial comparing weight loss maintenance interventions. The study included primary care patients, 18–75 yr old, with ≥5% intentional weight loss via lifestyle change in the past 2 yr. Participants (74% female, 87% white) were 53 ± 12 yr of age, had a body mass index of 30.4 ± 5.9 kg·m −2, and had a recent weight loss of 11% ± 8% (mean ± SD). Dietary habits were measured by the Diet Habits Survey. Physical activity and sedentary behavior were measured by self-report and objectively by pedometer. On average, participants reported high fruits and vegetables intake (five servings per day) and low intake of fried foods (one serving per week), desserts (one serving per week), and sugar-sweetened beverages (zero servings per week). Those with greater versus lesser weight loss had higher intake of fruits and vegetables ( P = 0.037) and low-fat foods or recipes ( P = 0.019). Average self-reported moderate-vigorous physical activity was 319 ± 281 min·wk −1, with significant differences between greater (374 ± 328 min·wk −1 ) versus lesser (276 ± 230 min·wk −1 ) weight loss groups ( P = 0.017). By pedometer, 30% had ≥7500 steps per day; the proportion was higher in greater (43%) versus lesser (19%) weight loss groups ( P = 0.005). For weight loss, clinical patients typically use simple strategies such as five or more fruits and vegetables per day, fried foods and desserts ⩽1·wk −1, elimination of sugary drinks, choosing low-fat foods/recipes, and physical activity 45–60 min·d −1 .